2008
DOI: 10.1007/s12161-008-9025-4
|View full text |Cite
|
Sign up to set email alerts
|

Current Methods for Extraction and Concentration of Enteric Viruses from Fresh Fruit and Vegetables: Towards International Standards

Abstract: Virus-contaminated soft fruits or vegetables are increasingly identified as causes of foodborne viral illness. Noroviruses and hepatitis A virus are the most common pathogens in viral infections transmitted by these kinds of foods. To improve microbiological detection and monitoring and to increase insights into the contribution of fruits and vegetables to foodborne viral transmission, sensitive, reliable, and standardized methods are needed. More studies on virus detection methods for foods are being publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 108 publications
0
35
0
1
Order By: Relevance
“…Methods that have currently been developed and optimized for virus detection from fruit and salad vegetables focus on elution of the virus from the surface (Croci et al 2008). A number of washing procedures and buffer systems have been described for the recovery of viruses from fruits and vegetables.…”
Section: Virus Release From Food Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods that have currently been developed and optimized for virus detection from fruit and salad vegetables focus on elution of the virus from the surface (Croci et al 2008). A number of washing procedures and buffer systems have been described for the recovery of viruses from fruits and vegetables.…”
Section: Virus Release From Food Matricesmentioning
confidence: 99%
“…A number of washing procedures and buffer systems have been described for the recovery of viruses from fruits and vegetables. The average recovery rates vary depending on the food matrix and virus (Croci et al 2008). Dubois et al (2007) described a protocol that included the rinsing of fruit and vegetable surfaces with a buffer of pH 9.5, supplemented with 100 mM Tris, 50 mM glycine, and 1% beef extract, a protein-and nucleic acid-rich substance.…”
Section: Virus Release From Food Matricesmentioning
confidence: 99%
“…In this study, using three different types of foods, i.e. strawberries, lettuce and shellfish, which have been implicated in several outbreaks of viral disease (Baker et al 2010;Maunula et al 2009;Grotto et al 2004;Ethelberg et al 2010) and which have often been found to contain inhibitory substances (Croci et al 2008), the SPC showed that the performance of the molecular-based analytical procedure for enteric viruses could be verified (concentration, nucleic acid extraction and nucleic acid amplification steps). However the use of an IAC in addition to SPC will allow more precise troubleshooting.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, detection of the presence of enteric viruses in foods is an important issue in food safety, and rapid and robust diagnostic methodology is needed (Greening and Hewitt 2008;Bosch et al 2011;Croci et al 2008). Molecularbased methods have become the typical diagnostic approach for the detection of foodborne viruses (Bosch et al 2011;Rodríguez-Lázaro et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Primary concentration: Viruses were eluted and concentrated from foods surface and crude sap samples via: 150 ml of 10 % (w/v) beef extract was added to 100 g raw fresh foods and to 100 ml crude sap samples, the mixtures were stirred for 30 min at room temperature and centrifuged at 12000 rpm for 15 min at room temperature (Croci et al, 2008). The pellet was discarded and the supernatant was then concentrated by organic flocculation method.…”
Section: Concentration Of Virusmentioning
confidence: 99%